The Role of the Latupati Institution in Overcoming Religious and Social Conflicts in Maluku in 1999 - Rahawarin, Yunus; Darakay, Jurnie; Rumlus, Clementina; Manuputty, Feky (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2021)
This study aims to explore the role of the Latupati institution in the Leihitu area in resolving the Maluku social and religious conflicts in 1999. This study used a qualitative method with a case study approach, the data sources were taken through direct interviews with ten informants consisting of the chairman of the traditional council assembly. Latupati Maluku, secretary of state, education, religion, customs and community leaders. All data were then analyzed thematically using NVivo 10 qualitative analysis software. The results showed that there were four ways that Latupati did in resolving conflicts, the four strategies were (i) making customary law a unifying tool for the community, (ii) carrying out dialogue between figures religion, education and customs, (iii) making agreements between communities to respect ancestral customs, (iv) making the Latupati customary institution a forum for interacting with the kings of all countries to find solutions to problems faced by the community. The results of this study have proven that the role of the Latupati customary institution is very real and successful in resolving religious and social conflicts in Maluku that occurred in 1999. This method can certainly be a reference for other regions in Indonesia in resolving conflicts in the community.